An exact spectral dynamic stiffness theory for composite plate-like structures with arbitrary non-uniform elastic supports, mass attachments and coupling constraints. (10th May 2016) - Liu, X.; Kassem, H.I.; Banerjee, J.R.
Abstract: This paper presents an exact spectral dynamic stiffness (SDS) theory for composite plates and plate assemblies with arbitrary non-uniform elastic supports, mass attachments and elastic coupling constraints. The theory treats the above supports, attachments and constraints in a sufficiently general, but accurate manner, which can be applied to various SDS formulations as well as classical dynamic stiffness formulations for both modal and dynamic response analysis. The methodology is concise but can be easily applied to complex plate-like structures with any arbitrary boundary conditions. It retains all the advantages of a recently developed SDS method which gives exact results with excellent computation efficiency. The results computed by the present theory are validated against published results. In order to demonstrate the practical applicability of the theory, three wide ranging engineering composite structures are investigated. For benchmarking purposes, results computed from the current theory are accurate up to the last figure quoted.